2022
DOI: 10.3389/fsurg.2022.992641
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of the prognostic nutritional index in patients with pancreatic cancer who underwent curative resection without preoperative neoadjuvant treatment: A systematic review and meta-analysis

Abstract: BackgroundThe prognostic nutrition index (PNI), which has been evaluated in various kinds of cancers, offered a simple yet effective approach to predict the prognosis. The aim of this meta-analysis is to reveal the correlation between preoperative PNI and the prognosis of patients with pancreatic ductal adenocarcinoma (PDAC) who underwent curative resection.MethodsWe searched the PubMed, Embase, Web of Science and Cochrane Library databases, and extracted the hazard ratio (HR) with 95% confidential interval (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…A recent meta-analysis with ∼2300 patients from seven studies found that high CONUT score (HR of 1.56) was able to predict OS in patients with PC. 55 Another meta-analysis 56 that included 14 studies of ∼3500 patients, found that low preoperative PNI was related to poor OS (HR 1.67) and RFS (HR 1.4) in PC patients who underwent curative resection without preoperative neoadjuvant treatment. 56 Xie et al conducted a meta-analysis with nine studies ( n = 2153 patients) and found that low GNRI was associated with poor OS in patients with gastrointestinal cancer (HR = 1.94) and a higher risk of complications (OR = 2.19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis with ∼2300 patients from seven studies found that high CONUT score (HR of 1.56) was able to predict OS in patients with PC. 55 Another meta-analysis 56 that included 14 studies of ∼3500 patients, found that low preoperative PNI was related to poor OS (HR 1.67) and RFS (HR 1.4) in PC patients who underwent curative resection without preoperative neoadjuvant treatment. 56 Xie et al conducted a meta-analysis with nine studies ( n = 2153 patients) and found that low GNRI was associated with poor OS in patients with gastrointestinal cancer (HR = 1.94) and a higher risk of complications (OR = 2.19).…”
Section: Discussionmentioning
confidence: 99%
“…55 Another meta-analysis 56 that included 14 studies of ∼3500 patients, found that low preoperative PNI was related to poor OS (HR 1.67) and RFS (HR 1.4) in PC patients who underwent curative resection without preoperative neoadjuvant treatment. 56 Xie et al conducted a meta-analysis with nine studies ( n = 2153 patients) and found that low GNRI was associated with poor OS in patients with gastrointestinal cancer (HR = 1.94) and a higher risk of complications (OR = 2.19). 57 While these nutritional indices show correlation with outcomes in patients with PC, the use of these indices has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Eight systemic immune-inflammation indices in the existing literature were computed based on laboratory examination results prior to the HD access procedures, including neutrophil-to-lymphocyte ratio (NLR), derived neutrophil-to-lymphocyte ratio (dNLR), albumin-toalkaline phosphatase ratio (AAPR), systemic inflammation response index (SIRI), systemic immune-inflammation index (SII), prognostic nutritional index (PNI), platelet-to-lymphocyte ratio (PLR), and lung immune prognostic index (LIPI) (12,(20)(21)(22)(23) (see the details of calculation in Supplementary Table 1).…”
Section: Collected Variablesmentioning
confidence: 99%
“…По данным систематического обзора и метаанализа 14 рандомизированных исследований, включавших 3385 больных, оперированных по поводу рака ПЖ, низкий PNI был ассоциирован с низкой послеоперационной выживаемостью [11].…”
Section: Abstract: Nutritional Support Nutritional Status Body Mass I...unclassified